The Role of Technology in Ownership Transfer - Podlipnik Giacomelli, Lana; Deu, Domen (Izzivi prenosa vodenja na naslednjo generacijo v družinskem podjetju, 2025)
Ownership transfer in family businesses is a complex process affecting long-term success. This study examines how Dines Ltd. manages intergenerational transfer and integrates technology into this process. Data were collected through an interview with the company’s future leader and analyzed qualitatively, comparing findings with relevant literature. Results indicate that gradual transfer of responsibility and building trust between generations facilitate successful leadership succession. This approach gives the successor time to develop essential skills. Technology is crucial for maintaining competitiveness and supports the transfer process through digitalization and the use of artificial intelligence. AI is applied in marketing, communication, succession planning, and evaluating potential successors. However, challenges arise from the conservative attitude of older generations toward adopting new technologies, contrasting with the younger generation’s innovative approach. Encouraging an open environment for creativity can bridge this gap and enhance intergenerational cooperation.